2014
DOI: 10.1002/aur.1383
|View full text |Cite
|
Sign up to set email alerts
|

Family‐Based Clinical Associations and Functional Characterization of the Serotonin 2AReceptor Gene (HTR2A) in Autism Spectrum Disorder

Abstract: The serotonin 2A receptor gene (HTR2A) harbors two functional single nucleotide polymorphisms (SNPs) that are frequent in populations of African and European descent; rs6311, which affects mRNA expression, and rs6314, which changes the amino acid sequence of the encoded protein and affects the signaling properties of the receptor. Multiple clinical associations support a role for these SNPs in cognitive and neuropsychiatric phenotypes, although studies in autism spectrum disorder (ASD) remain equivocal. Here, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 55 publications
6
23
0
Order By: Relevance
“…Families were recruited as previously reported (Cottrell et al, 2011; Smith et al, 2014). Caucasian participants with ADI-R scores and genetic material were used for the current analyses (74 boys, 14 girls, N=88).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Families were recruited as previously reported (Cottrell et al, 2011; Smith et al, 2014). Caucasian participants with ADI-R scores and genetic material were used for the current analyses (74 boys, 14 girls, N=88).…”
Section: Methodsmentioning
confidence: 99%
“…Genomic DNA was isolated and SNPs genotyped as previously reported (Smith et al, 2014). Briefly, genomic DNA was extracted from either whole blood or saliva.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low levels of RORA causes dysregulation of these genes and associated pathways. Prefrontal cortex and cerebellum tissue was used.[350]ATPBrain tissue (ATP)153 families (other)54 subjects (ATP)Functional characterisation studyVariant of the HTR2A gene rs6311 in ASD patients has lower level of expression and contains extended 5′untranslated region. Speculation that this variant could be a risk factor in ASD.…”
Section: Resultsmentioning
confidence: 99%
“…Case-control studies involving −1438 A/G polymorphism have demonstrated overrepresentation of G allele in the autistic than in the control group (Abdelrahman et al, 2014;Hranilovic et al, 2010). Family based study conducted by Smith et al (2014) also suggested significant under-transmission of minor A allele to offspring with ASD. A previous study by the same group showed that −1438 A allele decreased the expression of HTR2A mRNA with an extended 5 untranslated region (UTR) in the frontopolar cortex of the brain (Smith et al, 2013).…”
Section: Serotonin Receptorsmentioning
confidence: 99%